Mammals’ sperm microbiome: current knowledge, challenges, and perspectives on metagenomics of seminal samples - Contreras, María José; Núñez-Montero, Kattia; Bruna, Pablo; Zárate, Ana; Pezo, Felipe; García, Matías; Leal, Karla; Barrientos, Leticia (Frontiers in Microbiology, 2023)
Bacterial growth is highly detrimental to sperm quality and functionality. However, during the last few years, using sequencing techniques with a metagenomic approach, it has been possible to deepen the study of bacteria-sperm relationships and describe non-culturable species and synergistic and antagonistic relationships between the different species in mammalian animals. We compile the recent metagenomics studies performed on mammalian semen samples and provide updated evidence to understand the importance of the microbial communities in the results of sperm quality and sperm functionality of males, looking for future perspectives on how these technologies can collaborate in the development of andrological knowledge.